2002
DOI: 10.1177/104973202129119928
|View full text |Cite
|
Sign up to set email alerts
|

“You can’t Cure it so you have to Endure it”: The Experience of Adaptation to Diabetic Renal Disease

Abstract: In this study, the experience of adaptation to diabetic renal disease was examined from a phenomenological perspective. Twenty patients attending a diabetic renal clinic were interviewed in depth. Through the use of a template analysis approach, a set of strong themes relating to changes in lifestyle was identified: changes in the nature of involvement with the medical system, coping strategies, and hopes, fears, and expectations. Almost all participants attempted to construct a "good adaptation" in the face o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 28 publications
2
76
0
Order By: Relevance
“…Others have used Template Analysis to code similar types of qualitative data. 19,[21][22][23] In Template Analysis, thematic categories are predetermined a priori according to the researchers' study goals (e.g., physicians' opinions of WHI and their counseling strategies around HT discontinuation). Categories are usually organized in a hierarchical fashion, with more global overarching themes encompassing more specific categories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have used Template Analysis to code similar types of qualitative data. 19,[21][22][23] In Template Analysis, thematic categories are predetermined a priori according to the researchers' study goals (e.g., physicians' opinions of WHI and their counseling strategies around HT discontinuation). Categories are usually organized in a hierarchical fashion, with more global overarching themes encompassing more specific categories.…”
Section: Discussionmentioning
confidence: 99%
“…Categories are usually organized in a hierarchical fashion, with more global overarching themes encompassing more specific categories. 19 Multiple readings and coding of transcripts and modifications to the coding template proceed in an iterative fashion. Initial coding templates are modified based on coding the transcripts and comparing revised templates with other coders; new codes are added when data do not fit conceptually within the predetermined categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Themes which permeate several distinct clusters are sometimes referred to as "integrative themes." For example, in a study of the experience of diabetic renal disease, King et al (2002) identified "stoicism" and "uncertainty" as integrative themes because these aspects of experience tended to infuse much of the discussion whatever the foreground issue. 4.…”
Section: What Is Template Analysis?mentioning
confidence: 99%
“…McKee et al (2002), for instance, in a study of the frail elderly, obtained very low response rates for a number of quality-of-life measures used among this population. Irrespective of other data obtained, such rates suggest that in many cases, the instruments employed provide limited opportunity for people to describe personal experience in terms relevant to them (see also King, Carroll, Newton, & Dornan, 2002).…”
Section: Discussionmentioning
confidence: 99%